Some new conditions for the solvability of the cauchy problem for systems of linear functional-differential equations - Dil'na, N. Z.; Ronto, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We establish efficient conditions sufficient for the unique solvability of certain classes of Cauchy problems for systems of linear functional-differential equations. The conditions obtained are optimal in a certain sense.